Effect of workplace violence on health workers injuries and workplace absenteeism in Bangladesh - Md. Shahjalal; Md. Parvez Mosharaf; Rashidul Alam Mahumud (BMC, 2023)
Abstract Background Workplace violence (WPV) is an emerging problem for health workers (HWs) and a global concern in health systems. Scientific literatures infer that WPV against HWs is often attributed to workplace injuries and absenteeism, leading to a series of adverse consequences. Therefore, this study aimed to investigate the prevalence of workplace injuries and absenteeism due to WPV among Bangladeshi HWs and its association with factors related to health facilities, work environments, and rotating shift work. Methods This study used participants who had experienced WPV, including medical doctors, nurses, or any form of medical staff. A total of 468 victim HWs were added in the analytical exploration. Participants were generated from our previous cross-sectional study of 1081 Bangladeshi HWs. A logistic regression model was used to find the association between workplace injuries and absenteeism due to WPV among HWs and associated factors. Results The prevalence of workplace injuries and absenteeism due to WPV among HWs were 14.10% (95% CI 11.23-7.57) and 22.44% (95% CI 18.87-26.45), respectively. Injury incidence was higher among males (17.67%) and young HWs (20.83%). Workplace absenteeism was more common among male HWs (25%) and those working in public hospitals (23.46%). The magnitude of injuries and absenteeism varied significantly by hospital departments. Workplace injury was significantly higher among HWs who worked in the emergency (AOR = 21.53, 95% CI 2.55-181.71), intensive care (AOR = 22.94, 95% CI 2.24-234.88), surgery (AOR = 17.22, 95% CI 1.96-151.39), and gynecology & obstetrics departments (AOR = 22.42, 95% CI 2.25-223.07) compared with other departments. The burden of work-related absenteeism was significantly associated with HWs who worked in the emergency (AOR = 4.44, 95% CI 1.56-12.61), surgery (AOR = 4.11, 95% CI 1.42-11.90), and gynecology and obstetrics departments (AOR = 5.08, 95% CI 1.47-17.50). Conclusions This study observed a high prevalence of workplace injuries and absenteeism among HWs due to WPV across hospital departments, including emergency, surgery, intensive care and gynecology & obstetrics units. Policymakers should incorporate suitable strategies into Bangladesh's national health policy to combat violence in healthcare settings.